Long‐term effect of remote ischemic conditioning on infarct size and clinical outcomes in patients with anterior ST‐elevation myocardial infarction. Issue 3 (7th February 2020) - Verouhis, Dinos; Sörensson, Peder; Gourine, Andrey; Henareh, Loghman; Persson, Jonas; Saleh, Nawzad; Settergren, Magnus; Sundqvist, Martin; Tengbom, John; Tornvall, Per; Witt, Nils; Böhm, Felix; et al.
Abstract: Background: Conflicting evidence exists concerning the cardioprotective efficacy of remote ischemic conditioning as an adjunct to primary percutaneous intervention (PCI) in ST‐elevation myocardial infarction (STEMI) and data on long‐term outcomes are scarce. We evaluated final infarct size by cardiac magnetic resonance (CMR) performed 6 months after anterior STEMI treated with remote ischemic conditioning and clinical outcomes up to 3 years after the event. Methods: One hundred and fifteen patients with anterior STEMI were randomized to remote ischemic per‐postconditioning (RIperpostC) or sham procedure as adjunct to primary PCI. The primary outcome was myocardial salvage index (MSI) on CMR 6 months after the event. Secondary outcomes were absolute infarct size, left ventricular function, cardiac mortality, major adverse cardiac and cerebrovascular events (MACCE—composite of all‐cause mortality, myocardial infarction, readmission for heart failure, ischemic stroke, and target lesion revascularization) and all the individual components of MACCE. Results: There was no difference in MSI or left ventricular function between the RIperpostC and the control group after 6 months. Nor did clinical outcomes at 6 months or 3 years differ between the groups. Conclusions: RIperpostC as an adjunct to PCI in anterior STEMI did not result in better MSI or left ventricular function 6 months after the event. Furthermore, clinical outcomes at 6 months and 3 years were not altered.